Pet ownership, pet-related characteristics, and sleep quality among older adults in China: a nationwide cross-sectional study - Tang, Yixin; Zhu, Nini; Jin, Mengqi; Ren, Zhangqing; Lu, Jianliang; Xu, Lili; Xie, Lijun; Pan, Jianjiang (Frontiers in Veterinary Science, 2026)
IntroductionAs population aging accelerates globally, sleep disorders among older adults have become a significant public health concern. While pet ownership is increasingly recognized for its psychosocial benefits, its specific impact on sleep quality remains inconclusive. This study aimed to investigate the associations between pet ownership, diverse pet-related characteristics, and sleep quality among the elderly in China.MethodsA nationwide cross-sectional study was conducted involving 1,434 Chinese participants aged 60 and above (mean age: 71.0 ± 7.0 years). Sleep quality was assessed using the Athens Insomnia Scale (AIS). Multivariate logistic regression models were employed to estimate the adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for insomnia risk, adjusting for sociodemographic factors, health status, and lifestyle habits.ResultsPet ownership was significantly associated with a reduced risk of insomnia (adjusted OR = 0.75, 95% CI: 0.59–0.96). Specifically, dog ownership (OR = 0.63, 95% CI: 0.40–0.98) and owning healthy pets (OR = 0.41, 95% CI: 0.23–0.70) were protective factors. Conversely, rabbit ownership (OR = 1.94, 95% CI: 1.04–3.59), ownership duration of less than one year, and daily interaction exceeding two hours were associated with an increased risk of poor sleep quality. Frequent dog walking was also found to be beneficial for sleep health.DiscussionOur findings demonstrate that the pet-sleep relationship in older adults is complex and contingent on specific ownership contexts, suggesting that targeted pet companionship may serve as a potential intervention for sleep health in aging populations.